Investigation of actual exposure to facial sheet mask preceding its risk assessment - Zhou, Lihong; Chen, Jian; Chen, Tian; Chang, Huailong; Cui, Wenguang; She, Yuanyuan; Li, Zhu; Tang, Wenhua; Yuan, Dengfeng; Chen, Zhitao; Su, Jin (Scientific reports, 2022)
The present study aimed to reveal the amount per application of facial sheet masks and its influencing factors in Chinese population to form the base for an accurate exposure assessment. A total of 175 healthy subjects aged 18 years or older were recruited and divided into two subgroups: one group of 35 subjects were asked to apply same mask for 5, 10, 15, 20, 25, and 30 min respectively, and the other 140 subjects were instructed to apply one of four types of facial sheet masks presented in the market for 15 min. Furthermore, phenoxyethanol and methylparaben were measured to reflect actual exposure to chemicals. The sharp increase in the relative exposure to phenoxyethanol (CAS NO.122-99-6) and methylparaben at 25 min and longer suggests applying facial sheet masks for longer than 20 min may drive the exposure to hazardous chemicals to increase significantly. The 90th percentile of amount per application for plant-cellulose, bamboo charcoal fiber, bio-cellulose, and binchotan charcoal fiber-based masks was 5.753, 5.371, 5.017, and 4.821 g respectively. In addition, men and subjects with sebaceous skin demonstrated lower amount per application compared to women and subjects with dry skin, respectively. Finally, our data showed that the larger the contacting area between face and mask, the more amount per application. We concluded that the appropriate time of application should be less than 20 min. And mask fabrics, gender, sebum content, and contacting area could significantly impact the risk assessment of facial sheet masks. Our data for the first time provides insights into a realistic risk assessment of facial sheet masks in Chinese population.